Non-enzymatic Electrochemical Sensing of 3-Hydroxybutyric Acid by Incorporating Manganese Oxide Modified Electrode and Nitroprusside Electrolyte. Issue 9 (1st September 2022) - Ngamaroonchote, Aroonsri; Karn-orachai, Kullavadee
Abstract : The development of 3-hydroxybutyric acid (3-HB) biosensors via electrochemical method is commonly based on the use of enzymes that usually display inherent instability. Here, a novel non-enzymatic 3-HB electrochemical sensor platform by incorporating manganese oxide nanoparticles (Mn2 O3 NPs) modified screen printed carbon electrode (SPCE) and sodium nitroprusside (SNP) electrolyte was reported for the first time. The mechanism of this sensor based on the formation of electroactive SNP-HB species with assistance of Mn2 O3 catalyst. By the enhanced electroactivity of the complex, 3-HB can be quantitatively measured based on the increased peak current and shifted peak potential in cyclic voltammograms of SNP reduction. SNP concentration and Mn2 O3 loading were optimized for maximum current response. The sensitivity of as-prepared sensor system was examined under different pH values (6.4–7.4) in the range of 0–10 mM 3-HB. The highest sensitivity of 39.07 μ A·mM −1 ·cm −2 and 5.84 mV·mM −1 with LOD of 0.5 mM was achieved at pH 7.4 of electrolyte solution. The proposed sensor provided favorable stability and selectivity against various interferents. In addition, the ability to quantitatively detect 3-HB in artificial urine was also demonstrated, suggesting that our sensor can be a promising candidate for practical applications.